A systematic review on voltage stability analysis in smart and islanded microgrid parallel inverters - Bangari, Sowmya Renuka; Shivaleelavathi, Bangalore Gangadharaiah (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
The development of a smart grid depends on measuring and communication technologies and gathering heterogeneous data from micro grid. This enormous data contains procedures and methods that make it easier to use vast data while also increasing computing complexity and security. Given the maturity of power electronics technology, the penetration of distributed generation in both on- and off-grid environments has advanced in ways that have never been seen. Any complicated power system, like the off-grid parallel inverters, requires a stability study that considers several state variables. The smart grid environment's rising complexity and data explosion necessitate more hardware, which raises costs and necessitates additional physical space. An introduction to the special issue on voltage stability of micro grids with parallel inverters in power systems is presented in this review paper. Self-synchronizing inverters known as parallel inverters do not require a reference from the main grid to synchronize with one another. There are several general analytical techniques and enhanced procedures covered. The similarities, functionality, applications, designs, benefits, drawbacks, and general effectiveness are then contrasted. The significant contribution of this in-depth review is to establish a strong foundation for subsequent research in the area.